Comparison of Radiography, Laser Fluorescence, and Visual Examination in Diagnosing Incipient OcclusalCaries of Permanent First Molars - Zahra Bahrololoomi; Fateme Ezoddini; Niloofar Halvani (Tehran University of Medical Sciences, 2016)
Objectives: Early diagnosis of incipient and non cavitated carious lesions is crucial for performing preventive treatments. The aim of this study was to compare the effi- ciency of three diagnostic methods of bite-wing radiography, DIAGNOdent, and visu- al examination in diagnosing the incipient occlusal caries of permanent first molars. Materials and Methods:  In this diagnostic cross-sectional study, 109 premanent first molar teeth of 31 patients aged 7-13 years were examined visually by bite-wing radi- ograghy, and DIAGNOdent. Scoring of visual and radiography examinations were based on the Ekstrand classification. Visual examination after pit and fissure opening was used as the gold standard. ROC curve (Receiver Operating Characteristics) was used to define the best cut-off point for DIAGNodent compareing with gold standard and inter-examiner reproductibility of visual, radiography were assessed using Kappa test and ICC (Intraclass Correlation) wase used for DIAGNOdent values. Results: The sensitivity of detecting caries that had extended into the enamel was 81.4%, 86.3%, and 81.4% for visual examination, DIAGNOdent, and radiography, respectively. Moreover, the specificity was 100%, 71.4%, and 100% for visual obser- vation, DIAGNOdent, and radiography, respectively in the enamel. The Kappa index for inter-examiner correlation was 0.7 and 0.8 for visual examination and radiog- raphy, respectively. The ICC (Intraclass Correlation) was 0.98 for the values read by DIAGNOdent. Conclusion: Visual examination is rendered as the first choice in the diagnosis of in- cipient caries. In suspicious cases, radiography and laser DIAGNOdent can be used as adjunct procedures.